Increased Total Serum Bilirubin Level Post-Ibuprofen Use Is Inversely Correlated with Neonates' Body Weight - Zon-Min Lee; Yao-Hsu Yang; Ling-Sai Chang; Chih-Cheng Chen; Hong-Ren Yu; Kuang-Che Kuo (MDPI AG, 2022)
Backgrounds: Drugs with the ability to displace bilirubin from albumin-binding sites subsequently leading to an increased bilirubin level may cause hyperbilirubinemia in neonates. Ibuprofen is commonly used to treat patent ductus arteriosus (PDA) in neonates, yet the use of ibuprofen has drawn mixed conclusions. We performed a retrospective study to determine how ibuprofen use influences the total serum bilirubin (TSB) level in neonates of differing birth weight (BW). Materials and methods: Neonates (including premature infants) born at Chang Gung Memorial Hospital, Taiwan during January 2004 to July 2020 were entered into this study. We recorded the phototherapy duration, including the initial day and end day, and determined the average influence of one-day phototherapy on TSB level. The highest monitored TSB level post-ibuprofen use minus the one measured prior to ibuprofen use was considered the TSB change following ibuprofen administration in this study, and the above-mentioned influence of daily phototherapy on the TSB level was used to correlate the results. Neonates with any of the following conditions were excluded: those who received ceftriaxone, those with intraventricular hemorrhage, and those infected with TORCH. Results: The average daily influence of phototherapy on the TSB level of neonates was −0.20 (−0.57~0.05) mg/dL, −0.28 (−0.84~0.13) mg/dL, −0.75 (−1.77~0.10) mg/dL, and −1.60 (−2.70~−0.50) mg/dL in neonates with BWs of <1 kg, 1-1.49 kg, 1.5-2.49 kg, and ≥2.5 kg, respectively, indicating that neonates with a BW ≥ 1.5 kg experienced a greater reduction in TSB level following phototherapy as compared with those with a BW < 1.5 kg. The average TSB increase following ibuprofen use in neonates was 3.38 ± 2.77 mg/dL, 2.04 ± 2.53 mg/dL, and 1.34 ± 2.24 mg/dL in neonates with BWs of <1 kg, 1-1.49 kg, and ≥1.5 kg, respectively, i.e., an elevated TSB change with a decreased neonate BW was noted post-ibuprofen use (p = 0.026, one-way analysis of variance (ANOVA)). Conclusions: As ibuprofen use is correlated with an apparent increase in TSB level in neonates with a lower BW, especially in those with a BW < 1 kg, iv acetaminophen can be an appropriate alternative to ibuprofen for ELBW neonates for the treatment of PDA if they are experiencing severe unconjugated hyperbilirubinemia.